Entre fios e dobras: o tecer da reforma psiquiátrica no município de Santa Maria/RS - Ramos, Luciane Silva (2009)
This master degree dissertation on nursery aimed to understand how the work is organized, in particular, the relations and the interaction in the Committee of Mental Health in Santa Maria, searching for evidences in acting as an intersection space in the consolidation of the psychiatric reform in Santa Maria. Such option occurred because the researcher took part actively in the process of implementation of the Mental Health Committee, representing the managers in the city, from the reality of services on mental health and from the need of (re)view the organization of the assistance in the city net. Thus, it is necessary to look over the micro politics in the process of the psychiatric reform I nth context of the Unique Health System (SUS, in Portuguese), in Santa Maria, aiming to perceive what happens over there, in the perspective of making this a space of the Committee of Mental Health, an intersection space, indicating a instituting relation. The theoretical fundaments are based on Merhy s reference, among other authors. The study approach was qualitative, like a case study, using the techniques of document analysis, systematic observation and focus group, adding up to 11 (eleven) people composing the Committee of Mental Health. The collected material was analyzed in accordance with, with the construction of four theme axis. Along with the results, it was identified that, since its creation, the Committee of Mental Health has become an important space of constant discussion among the services of mental health and, mainly, of the health units. It is pointed out that, from the Committee of Mental Health, the actions on the articulation between mental health and basic assistance actually started, by means of Mental Health in discussion , which originated the Assistance on Mental Health for the Basic Health Assistance . Therefore, collective spaces are chosen, like the Committee of Mental Health, because are concrete spaces, in time and space, directed for communication, for listening and for the circulation of information about desire, interest and aspects of reality as well as for the decision making, trying to make possible new instituting ways.